Increasing Planting Density with Reduced Topdressing Nitrogen Inputs Increased Nitrogen Use Efficiency and Improved Grain Quality While Maintaining Yields in Weak-Gluten Wheat - Wenyin Zhou; Suhui Yan; Abdul Rehman; Haojie Li; Shiya Zhang; Yudong Yong; Yang Liu; Longfei Xiao; Chengyan Zheng; Wenyang Li (Agriculture)
Increasing nitrogen fertilizer will increase wheat grain yield and grain quality at the same time, but the goal of high quality and stable yield in weak-gluten wheat production is to reduce grain protein content and increase grain yield. Our research goal is to reduce nitrogen input while increasing planting density to maintain high quality and stable yield. Field studies were conducted during two successive seasons using a widely planted cultivar, Yangmai 15. We studied the effects of reduced nitrogen topdressing and increased planting density on yield, quality and nitrogen agronomic efficiency. The field experiment was conducted with four nitrogen (N) levels for topdressing at jointing stage: 37.8 (N1), 43.2 (N2), 48.6 (N3) and 54 kg N ha−1 (N4). Moreover, there were three planting densities: 180, 240 and 300 × 104 plants ha−1 (D1, D2 and D3, respectively). When the amount of nitrogen topdressing was reduced, the number of tillers and spikes in each growth period of wheat decreased significantly, and the yield increased first and then decreased, with the highest yield at the level of 48.6 kg N ha−1. When the planting density was increased, the number of tillers and spikes in each growth period of wheat increased significantly, the yield increased significantly, and the yield was the highest at the level of 180 × 104 plants ha−1. Under the same density level, the flag leaf chlorophyll content, leaf area index, nitrogen production efficiency and nitrogen use efficiency decreased with a decrease in the nitrogen application rate. Under the same nitrogen topdressing amount, the nitrogen fertilizer production efficiency and nitrogen fertilizer utilization efficiency increased with the increase in density. The relative chlorophyll content, leaf area index, nitrogen partial factor productivity, nitrogen use efficiency, grain accumulation, grain distribution ratio and grain yield of wheat were the highest under the treatment of a planting density of 300 × 104 plants ha−1 and nitrogen topdressing amount of 48.6 kg N ha−1. The combined decrease in nitrogen recovery and increase in planting density decreased protein content, sedimentation value and wet gluten content. Increasing density significantly improved dry matter accumulation in the population, partially compensating for the yield loss due to nitrogen reduction by increasing the effective number of spikes, thereby further improving grain quality and nitrogen use efficiency. Therefore, agronomic approaches combining low nitrogen and high planting densities may be effective in simultaneously increasing grain yield and nitrogen use efficiency and stabilizing grain processing quality in weakly reinforced wheat.